Are You on the Right Platform? A Conjoint Analysis of Social Media Preferences in Aesthetic Surgery Patients. (13th September 2018) - Nayyar, Apoorve; Jadi, Jihane; Garimella, Roja; Elkins-Williams, Stephen Tyler; Gallagher, Kristalyn K; Kalliainen, Loree K; Hultman, Charles Scott; Wu, Cindy
Abstract: Background: Social media has become an indispensable tool for patients to learn about aesthetic surgery. Currently, procedure-specific patient preferences for social media platforms and content are unknown. Objectives: The authors sought to evaluate social media preferences of patients seeking aesthetic surgery. Methods: We utilized a choice-based conjoint analysis survey to analyze the preferences of patients seeking 3 common aesthetic procedures: breast augmentation (BA), facial rejuvenation (FR), and combined breast/abdominal surgery (BAB). Participants were asked to choose among social media platforms (Facebook, Twitter, Instagram, Snapchat, Pinterest, Tumblr, YouTube), information extent (basic, moderate, comprehensive), delivery mechanism (prerecorded video, live video, photographs, text description), messenger (surgeon, nurse/clinic staff, patient), and option for interactivity (yes/no). The survey was administered using an Internet crowdsourcing service (Amazon Mechanical Turk). Results: A total of 647 participants were recruited: 201 in BA, 255 in FR, and 191 in BAB. Among attributes surveyed, participants in all 3 groups (BA, FR, BAB) valued social media platform as the most important (30.9%, 33.1%, 31.4%), followed by information extent (23.1%, 22.9%, 21.6%), delivery mechanism (18.9%, 17.4%, 18%), messenger (16%, 17%, 17.2%), and interactivity (11.1%, 9.8%, 11.8%). Within these attributes, Facebook ranked as the preferred platform, with comprehensive information extent, live video as the delivery mechanism, and surgeon as the messenger as most preferred. Conclusions: The choice of social media platform is the most important factor for patients, and they indicated a preference for comprehensive information delivered by the surgeon via live video on Facebook. Our study elucidates social media usage in common aesthetic populations, which can help improve aesthetic patient outreach.